Electrolytic hydrogen production stainless steel pole net and preparation method and application thereof
Patent Information
- Application Number
- CN202410104320.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-25
AI Technical Summary
[0004]目前,贵金属基材料催化剂被认为是效率最高的析氧反应电催催化剂,但贵金属材料的稀缺性和较差的稳定性阻碍了它们的大规模实际应用
[0010]将所述刻蚀板在含硫和磷的气源中气相沉积后制得处理板,将所述处理板浸没在活性溶液中活化后制得活化板;
Smart Images

Figure BDA0004681207160000081 
Figure BDA0004681207160000091
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolytic hydrogen production technology, and in particular to a stainless steel electrode mesh for electrolytic hydrogen production, its preparation method, and its application. Background Technology
[0002] The rapid increase in carbon dioxide emissions has drawn widespread attention to the problem of global warming, and has also created an urgent need for sustainable clean energy. Among various clean energy sources, hydrogen energy is considered one of the most promising alternatives to fossil fuels due to its excellent energy density and environmental friendliness. Among existing methods for producing hydrogen, the electrocatalytic hydrogen evolution reaction in alkaline electrolytes has attracted widespread attention due to its high production safety and product purity.
[0003] The key issue in the electrochemical water splitting reaction lies in its energy consumption. Whether it's the oxygen evolution reaction (OER) at the anolyte or the hydrogen evolution reaction at the cathode (HER), the water electrolysis reaction still requires a relatively high overpotential, which significantly limits the efficiency of hydrogen production. Therefore, to reduce the overpotential of the water electrolysis reaction and decrease the amount of electrical energy required, exploring highly active electrocatalysts is an effective way to improve water electrolysis efficiency and reduce the hydrogen production overpotential.
[0004] Currently, noble metal-based catalysts are considered the most efficient electrocatalysts for the oxygen evolution reaction (OER). However, the scarcity and poor stability of noble metal materials hinder their large-scale practical application. To find inexpensive alternatives, significant research has been conducted on compounds such as transition metal alloys, oxides, and hydroxides. For example, NiSe2 transition metal chalcogenide nanosheets and bimetallic Ni3S2 / FeS composite materials can be used as electrocatalysts for water electrolysis to produce hydrogen. However, these materials struggle to maintain stable catalytic performance over long-term use, thus necessitating a solution to address this issue. Summary of the Invention
[0005] The purpose of this invention is to provide a stainless steel electrode mesh for electrolytic hydrogen production, its preparation method and application, which can not only reduce the overpotential in the electrocatalytic hydrogen evolution process, but also improve the overall stability of catalytic performance.
[0006] In a first aspect, the present invention provides a stainless steel electrode mesh for electrolytic hydrogen production, comprising an electrode mesh substrate and a high-entropy alloy layer formed on the surface of the electrode mesh substrate, wherein the high-entropy alloy layer comprises, by molar percentage, 10-20% Fe, 20-25% Ni, 15-20% Co, 15-20% Al and the balance Y.
[0007] The stainless steel electrode mesh for hydrogen production provided by this invention improves the overall durability of the stainless steel electrode mesh substrate by forming a high-entropy alloy layer on the electrode mesh substrate. At the same time, the high-entropy alloy layer and the electrode mesh substrate can be well combined to achieve a good electrolytic catalytic effect. This not only reduces the overpotential in the electrocatalytic hydrogen evolution process, but also improves the overall stability of catalytic performance.
[0008] Secondly, the present invention provides a method for preparing a stainless steel electrode mesh for electrolytic hydrogen production, comprising the following steps:
[0009] The electrode substrate is immersed in an acidic etching solution for etching reaction, and then removed and dried to obtain an etched board;
[0010] The etched plate is vapor-deposited in a gas source containing sulfur and phosphorus to obtain a treated plate, and the treated plate is activated by immersing it in an active solution to obtain an activated plate.
[0011] The activated plate was immersed in a metal salt solution, reacted under ultrasonic treatment at 200-250°C, and then calcined to obtain a stainless steel electrode mesh for electrolytic hydrogen production; the metal salt solution contained dissolved Fe. 2+ Ni 2+ Co 2+ Al 3+ and Y 3+ .
[0012] The preparation method provided by this invention involves pre-etching the electrode substrate in an acidic etching solution, which increases the active sites and surface area of the electrode substrate surface. This facilitates sulfur and phosphorus doping during vapor deposition. Further activation treatment of the processed plate in an active solution allows metal ions from the metal salt solution to enter the surface of the processed plate under solvothermal reaction, and after calcination, they can be reduced to a zero-valence high-entropy alloy layer. This improves the bonding tightness between the high-entropy alloy layer and the electrode substrate.
[0013] Optionally, when the electrode substrate is immersed in an acidic etching solution for etching, the solute in the acidic etching solution includes lithium chloride and calcium stearate, and the mass ratio of lithium chloride to calcium stearate is (2-3):(1-1.5).
[0014] Optionally, when immersing the electrode substrate in an acidic etching solution for etching, the process includes:
[0015] The electrode substrate was immersed in an acidic etching solution and kept at a temperature of 100-150℃ under a protective atmosphere.
[0016] After rotating the electrode substrate to disturb the acidic etching solution for 1-2 hours, it is removed, cleaned, and dried to obtain the etched plate.
[0017] Optionally, when the etched plate is vapor-deposited in a sulfur- and phosphorus-containing gas source, the sulfur- and phosphorus-containing gas source includes hydrogen sulfide and phosphine, and the volume ratio of hydrogen sulfide to phosphine is 1:(1-2).
[0018] Optionally, during the activation process of immersing the treatment plate in an activation solution, the solute in the activation solution, by concentration, includes 3-5% sodium hydroxide, 1.5-3% sodium peroxide, and 2-3% potassium pyrophosphate.
[0019] Optionally, when the activation plate is immersed in the metal salt solution, the method for preparing the metal salt solution includes the following steps: stirring and dissolving ferrous sulfate, nickel sulfate, cobalt chloride, aluminum sulfate and yttrium chloride to obtain the metal salt solution.
[0020] Optionally, during the reaction and calcination process at 200-250℃ and ultrasonic treatment, the reaction product is calcined at 700-900℃ for 10-12 hours in a hydrogen atmosphere to obtain an electrolytic hydrogen production stainless steel electrode mesh.
[0021] Optionally, when the electrode mesh substrate is immersed in an acidic etching solution for etching, the thickness of the electrode mesh substrate is 1-3 mm.
[0022] Thirdly, the present invention also provides the application of the stainless steel electrode mesh for electrolytic hydrogen production prepared by any of the above-mentioned optional preparation methods in electrolytic hydrogen production. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0024] This invention provides a stainless steel electrode mesh for hydrogen electrolysis, comprising an electrode mesh substrate and a high-entropy alloy layer formed on the surface of the electrode mesh substrate. The high-entropy alloy layer comprises, by molar percentage, 10-20% Fe, 20-25% Ni, 15-20% Co, 15-20% Al, and the balance Y. In fact, all metal ions in the high-entropy alloy layer exist in a zero-valence state. Simultaneously, during the hydrogen evolution reaction in water electrolysis, the stainless steel electrode mesh serves as the cathode, the electrode mesh substrate acts as a support to improve the overall structural strength, and the high-entropy alloy layer serves as a catalytic active site for water electrolysis.
[0025] This invention also provides a method for preparing a stainless steel electrode mesh for hydrogen electrolysis, comprising the following steps:
[0026] S1. Etching and Activation: The electrode substrate is immersed in an acidic etching solution for etching reaction, and then taken out and dried to obtain an etched board;
[0027] S2. Vapor deposition: The etched plate is vapor-deposited in a gas source containing sulfur and phosphorus to obtain a treated plate, and the treated plate is activated by immersing it in an active solution to obtain an activated plate.
[0028] S3. Alloy forming: The activated plate is immersed in a metal salt solution, reacted at 200-250℃ under ultrasonic treatment, and then calcined to obtain an electrolytic hydrogen production stainless steel electrode mesh.
[0029] In some embodiments, during the etching activation process in step S1, the solutes in the acidic etching solution include lithium chloride and calcium stearate, and the mass ratio of lithium chloride to calcium stearate in the acidic etching solution is (2-3):(1-1.5). Specifically, the acidic etching solution also includes at least one of dilute hydrochloric acid, dilute nitric acid, dilute sulfuric acid, and phosphoric acid, which are used to adjust the acidic etching solution to be acidic.
[0030] In some embodiments, the thickness of the electrode substrate used in step S1 etching activation is 1-3 mm. In practice, the surface of the electrode substrate can be degreased and polished using acetone or other organic solvents before performing step S1 etching activation.
[0031] In some embodiments, the etching activation process in step S1 includes: immersing the electrode substrate in an acidic etching solution and keeping it warm under a protective atmosphere of 100-150°C; rotating the electrode substrate to disturb the acidic etching solution for 1-2 hours, then removing it, cleaning and drying it to obtain an etched plate.
[0032] Specifically, when etching is performed in a protective atmosphere at 100-150°C, the protective atmosphere can be an inert gas, such as argon.
[0033] Specifically, during the process of immersing the electrode substrate in the acidic etching solution, the acidic etching solution completely submerges the electrode substrate, and all sides of the electrode substrate do not come into contact with the inner wall of the container holding the acidic etching solution.
[0034] Specifically, during the process of rotating the electrode substrate to agitate the acidic etching solution, the rotation speed of the electrode substrate is controlled at 10-20 rpm. This slow rotation can improve the uniformity of contact between the acidic etching solution and the surface of the electrode substrate, while avoiding deformation of the electrode substrate at high speeds.
[0035] In some embodiments, during the process of removing and drying the etched plate after performing the etching activation in step S1, the reaction product after the etching reaction is completed is rinsed with deionized water, anhydrous ethanol and sodium hydroxide solution, and then placed in a vacuum drying oven for vacuum drying to obtain the etched plate.
[0036] In fact, when performing step S2 vapor deposition, the etched plate is vapor deposited in a sulfur and phosphorus gas source. The sulfur and phosphorus gas source used includes hydrogen sulfide and phosphine, and the volume ratio of hydrogen sulfide to phosphine is 1:(1-2).
[0037] In some embodiments, when performing step S2 vapor deposition, in which the etched plate is vapor deposited in a gas source containing sulfur and phosphorus, the process includes: placing the etched plate in a CVD furnace, introducing a mixed gas of hydrogen sulfide and phosphine, performing vapor deposition at 500-700°C, and then cooling to room temperature to obtain the processed plate.
[0038] In some embodiments, during step S2 vapor deposition, which involves immersing the treatment plate in an activation solution for activation, the solutes in the activation solution include, by concentration, 3-5% sodium hydroxide, 1.5-3% sodium peroxide, and 2-3% potassium pyrophosphate. Immersing the treatment plate in the activation solution further exposes the active sites on the surface of the treatment plate.
[0039] In some embodiments, during step S2 vapor deposition, when the treatment plate is immersed in the activation solution for activation, the treatment plate is completely immersed in the activation solution, ultrasonically treated at 50-80°C for 30 minutes, then removed, cleaned, and dried to obtain the activated plate.
[0040] In some embodiments, the metal salt solution used in step S3, alloy forming, is prepared by stirring and dissolving ferrous sulfate, nickel sulfate, cobalt chloride, aluminum sulfate, and yttrium chloride to obtain the metal salt solution. Specifically, ferrous sulfate, nickel sulfate, cobalt chloride, aluminum sulfate, and yttrium chloride can all be dissolved and dispersed in the form of hydrated salts.
[0041] In some embodiments, when preparing the metal salt solution, ferrous sulfate, nickel sulfate, cobalt chloride, aluminum sulfate, and yttrium chloride are mixed in a specific molar ratio so that the metal ions in the resulting metal salt solution include 10-20% Fe. 2+ 20-25% Ni 2+ 15-20% Co 2+ 15-20% Al 3+ and the margin Y 3+ .
[0042] In some embodiments, during the alloy forming process in step S3, after reaction and calcination at 200-250°C and ultrasonic treatment, the reaction product is calcined at 700-900°C for 10-12 hours in a hydrogen atmosphere to obtain an electrolytic hydrogen production stainless steel electrode mesh.
[0043] This invention also provides a stainless steel electrolytic hydrogen production electrode mesh prepared by the preparation method in any of the above embodiments, comprising an electrode mesh substrate and a high-entropy alloy layer formed on the surface of the electrode mesh substrate. The high-entropy alloy layer comprises, by molar percentage, 10-20% Fe, 20-25% Ni, 15-20% Co, 15-20% Al, and the balance Y. By forming a high-entropy alloy layer on the electrode mesh substrate, the stainless steel electrode mesh substrate can improve the overall durability of the material. Simultaneously, the high-entropy alloy layer and the electrode mesh substrate can be well bonded to achieve a good electrolytic catalytic effect, not only reducing the overpotential in the electrocatalytic hydrogen evolution process but also improving the overall catalytic performance stability.
[0044] In fact, the present invention also provides an application of the electrolytic hydrogen production stainless steel electrode mesh prepared by the preparation method in any of the above embodiments in electrolytic hydrogen production. Specifically, it includes the following steps: using a graphite rod as the anode, the electrolytic hydrogen production stainless steel electrode mesh as the cathode, and using a 1 mol / L KOH solution as the electrolyte for electrolytic hydrogen production.
[0045] Example 1
[0046] This embodiment 1 provides a method for preparing a stainless steel electrode mesh for electrolytic hydrogen production, including the following steps:
[0047] S1. Etching and Activation: The surface of the 304 stainless steel electrode substrate is cleaned with acetone, then polished with 500-grit sandpaper, cleaned and dried to obtain a pretreated electrode substrate. The pretreated electrode substrate is completely immersed in an acidic etching solution. Under an argon atmosphere at 120°C, the electrode substrate is rotated at 15 rpm to agitate the acidic etching solution. After stirring and reacting for 2 hours, the electrode substrate is removed, rinsed with anhydrous ethanol and sodium hydroxide aqueous solution, and then vacuum dried to obtain an etched plate.
[0048] S2. Vapor Deposition: The etched plate is placed in the furnace chamber of a CVD furnace. After evacuation, the temperature is increased to 600°C at a heating rate of 5°C / min. Hydrogen sulfide and phosphine gases with a volume ratio of 1:1 are introduced into the CVD furnace, and the flow rates of hydrogen sulfide and phosphine gases are controlled at 1 slm. After vapor deposition for 30 min, the plate is cooled to room temperature with the furnace to obtain the processed plate. The processed plate is then immersed in an activation solution and activated for 30 min at 60°C and 250W ultrasonic power. After that, it is taken out, rinsed with deionized water, and dried to obtain the activated plate.
[0049] S3. Alloy forming: 1.5 mol ferrous sulfate, 2.3 mol nickel sulfate, 2 mol cobalt chloride, 0.9 mol aluminum sulfate and 2.4 mol yttrium chloride were dissolved in deionized water to prepare a metal salt solution. The activation plate was immersed in the metal salt solution and reacted at 200-250℃ under ultrasonic treatment for 8 hours. The reaction product was then transferred to a hydrogen atmosphere at 800℃ and calcined for 10 hours. After cooling to room temperature, the stainless steel electrode mesh for electrolytic hydrogen production was obtained.
[0050] In Example 1, the acid etching solution used in step S1 contains lithium chloride and calcium stearate in a mass ratio of 2:1, and also contains dilute hydrochloric acid to make the acid etching solution acidic; the activation solution used in step S2 contains 3% sodium hydroxide, 2% sodium peroxide and 2% potassium pyrophosphate in terms of concentration.
[0051] Comparative Example 1
[0052] Comparative Example 1 provides a method for preparing a stainless steel electrode mesh for hydrogen production by electrolysis, comprising the following steps:
[0053] D1. Etching and Activation: The surface of the 304 stainless steel electrode substrate is cleaned with acetone, then polished with 500-grit sandpaper, cleaned and dried to obtain a pretreated electrode substrate. The pretreated electrode substrate is completely immersed in an acidic etching solution. Under an argon atmosphere at 120°C, the electrode substrate is rotated at 15 rpm to agitate the acidic etching solution. After stirring and reacting for 2 hours, the electrode substrate is removed, rinsed with anhydrous ethanol and sodium hydroxide aqueous solution, and then vacuum dried to obtain an etched plate.
[0054] D2. Vapor deposition: The etched plate is placed in the furnace chamber of the CVD furnace. After evacuation, the temperature is raised to 600°C at a heating rate of 5°C / min. Hydrogen sulfide gas and phosphine gas with a volume ratio of 1:1 are introduced into the CVD furnace, and the flow rates of hydrogen sulfide gas and phosphine gas are controlled to be 1 slm. After vapor deposition for 30 min, the furnace is cooled to room temperature to obtain the electrolytic hydrogen production stainless steel electrode mesh.
[0055] Performance testing
[0056] The stainless steel electrolytic hydrogen production electrode mesh prepared in Example 1 and Comparative Example 1 was used as the cathode, and the graphite rod as the anode. A 1 mol / L KOH solution was used as the electrolyte, and the electrode was operated at 100 mA / cm². 2 and 300mA / cm 2 The overpotential of the electrolytic hydrogen production stainless steel electrode prepared in Example 1 was tested at a current density, and the results are shown in Table 1. The overpotential of the electrode prepared in Example 1 was then tested after being immersed in a saturated sodium chloride solution for 168 hours, and the results are shown in Table 1.
[0057] Table 1. Hydrogen evolution performance of the stainless steel electrode meshes prepared in Example 1 and Comparative Example 1 for hydrogen production via electrolysis.
[0058]
[0059]
[0060] As can be seen from Table 1, the electrolytic hydrogen production stainless steel electrode mesh prepared by the preparation method provided by the present invention not only has good hydrogen evolution activity, but also maintains structural integrity and hydrogen evolution performance even after long-term immersion in saturated sodium chloride solution.
[0061] While embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations fall within the scope and spirit of the invention as set forth in the claims. Furthermore, the invention described herein may have other embodiments and can be implemented or carried out in various ways.
Claims
1. A method for preparing a stainless steel electrode mesh for electrolytic hydrogen production, characterized in that, Includes the following steps: The electrode substrate is immersed in an acidic etching solution for etching reaction, and then removed and dried to obtain an etched board; The etched plate is vapor-deposited in a gas source containing sulfur and phosphorus to obtain a treated plate, and the treated plate is activated by immersing it in an active solution to obtain an activated plate. The activated plate was immersed in a metal salt solution, reacted under ultrasonic treatment at 200-250°C, and then calcined to obtain a stainless steel electrode mesh for electrolytic hydrogen production; the metal salt solution contained dissolved Fe. 2+ Ni 2+ Co 2+ Al 3+ and Y 3+ The electrolytic hydrogen production stainless steel electrode grid includes an electrode grid substrate and a high-entropy alloy layer formed on the surface of the electrode grid substrate. The high-entropy alloy layer includes 10-20% Fe, 20-25% Ni, 15-20% Co, 15-20% Al and the balance Y by molar percentage.
2. The preparation method according to claim 1, characterized in that, When the electrode substrate is immersed in an acidic etching solution for etching, the solute in the acidic etching solution includes lithium chloride and calcium stearate, and the mass ratio of lithium chloride to calcium stearate is (2-3):(1-1.5).
3. The preparation method according to claim 1, characterized in that, When the electrode substrate is immersed in an acidic etching solution for etching, the process includes: The electrode substrate was immersed in an acidic etching solution and kept at a temperature of 100-150℃ under a protective atmosphere. After rotating the electrode substrate to disturb the acidic etching solution for 1-2 hours, it is removed, cleaned, and dried to obtain the etched plate.
4. The preparation method according to claim 1, characterized in that, When the etching plate is vapor-deposited in a sulfur- and phosphorus-containing gas source, the sulfur- and phosphorus-containing gas source includes hydrogen sulfide and phosphine, and the volume ratio of hydrogen sulfide to phosphine is 1:(1-2).
5. The preparation method according to claim 1, characterized in that, During the activation process of immersing the treatment plate in the activation solution, the solute in the activation solution, by concentration, includes 3-5% sodium hydroxide, 1.5-3% sodium peroxide, and 2-3% potassium pyrophosphate.
6. The preparation method according to claim 1, characterized in that, When the activation plate is immersed in the metal salt solution, the method for preparing the metal salt solution includes the following steps: stirring and dissolving ferrous sulfate, nickel sulfate, cobalt chloride, aluminum sulfate and yttrium chloride to obtain the metal salt solution.
7. The preparation method according to claim 1, characterized in that, After the reaction is carried out at 200-250℃ and ultrasonic treatment, the reaction product is calcined at 700-900℃ for 10-12 hours in a hydrogen atmosphere to obtain an electrolytic hydrogen production stainless steel electrode mesh.
8. The preparation method according to claim 1, characterized in that, When the electrode substrate is immersed in an acidic etching solution for etching, the thickness of the electrode substrate is 1-3 mm.
9. The application of a stainless steel electrode mesh for hydrogen production prepared by the preparation method according to any one of claims 1 to 8 in hydrogen production by electrolysis.
Citation Information
Patent Citations
Method for improving electrocatalytic hydrogen evolution performance of high-entropy alloy through heat treatment
CN115652228A
Preparation method of stainless steel electrode net electrocatalyst for electrolytic hydrogen production
CN115710723A